Pattern of anti-diabetic treatment and its relation with glycaemic control among diabetic patients in a tertiary care hospital of Bangladesh (BIRDEM Medical Journal, 2021)
Background: The main determinants of diabetes management, therapeutic habits and glycaemic control are likely to differ between populations. The pharmacological armamentarium to treat hyperglycaemia in type 2 diabetes mellitus (T2DM) has changed substantially over the past few years with the development of new therapeutic agents. This study evaluated relationships between pattern of pharmacological treatment and glycaemic control in patients with T2DM.Methods: This cross-sectional study was carried out among 486 T2DM patients attending the endocrinology outpatient clinic of MARKS Medical College & Hospital, Dhaka, Bangladesh during the period between July 2018 and June 2019. After obtaining written informed consent, both the treatment pattern and the degree of glycaemic control were estimated from T2DM patients. Glycosylated hemoglobin A1C (HbA1c) was determined by liquid chromatography. Glycaermic control categorized as fair control (HbA1c